Pelatihan dan Pendampingan bagi Peningkatan Kapasitas Aparat dan Institusi Desa dalam Perencanaan dan Implementasi Pembangunan - Setiadi Setiadi; Henny Ekawati; Fadlan Habib (Faculty of Cultural Sciences, 2020)
The implementation of Law No. 6 2014 faces obstacles due to the weak quality of village officials and institutions. This has an impact on the weakening role of the village government in its function as a development accelerator. It is necessary to increase the capacity of the apparatus in order to understand how development planning processes should be carried out at the village level, and how these processes are supported by strong village government institutions. In addition, there needs to be a control mechanism for the village government. This can be done by strengthening the role of the BPD. With the increased quality and capacity of village government apparatus and institutions, as well as strong civil society control played by the BPD, there will be a synergy in implementing good development at the village level. Village officials are no longer the sole player in village development. Efforts to create these ideal conditions continue to be in progress at the village level and will always be dynamic due to the influence of supralocal powers which are sometimes not in line with the development and will of the local community.====Implementasi UU No. 6 Tahun 2014 menghadapi kendala akibat lemahnya kualitas aparat dan kelembagaan desa. Hal ini berdampak pada semakin lemahnya peran pemerintah desa dalam fungsinya sebagai akselerator pembangunan. Perlu adanya peningkatan kapasitas aparat agar memahami bagaimana proses-proses perencanaan pembangunan harus dilakukan di tingkat desa serta bagaimana proses-proses tersebut didukung oleh kuatnya kelembagaan pemerintah desa. Selain itu, perlu ada mekanisme kontrol terhadap pemerintah desa. Hal ini bisa dilakukan dengan penguatan peran BPD. Dengan meningkatnya kualitas dan kapasitas aparat dan kelembagaan pemerintah desa serta kontrol masyarakat sipil yang kuat yang diperankan oleh BPD, akan ada sinergi pelaksanaan pembangunan yang baik di tingkat desa. Aparat desa tidak lagi menjadi pemain tunggal pembangunan desa. Upaya penciptaan kondisi ideal ini terus berproses di tingkat desa dan akan selalu dinamis akibat pengaruh kekuasaan supralokal yang terkadang tidak sejalan dengan perkembangan dan kehendak masyarakat lokal.